The Effectiveness of Cold Compress on Reducing Edema in Post-Filler Procedure Patients at the Aesthetic Lounge - Devita Angraeni; Siti Aminah (Green Publisher Indonesia, 2026)
This study aims to evaluate the effectiveness of cold compress on reducing edema in patients post facial filler procedures at Aesthetic Lounge Clinic. Edema is a common side effect following filler procedures, which can affect the patient's appearance. This research employed a pre-experimental design using the one group pretest-posttest method. Seventy patients who experienced edema after filler procedures were given a cold compress intervention for 10-15 minutes. The results showed that cold compress significantly reduced edema, both in scale and size. The Wilcoxon Signed Rank Test yielded a p-value < 0.05, indicating a significant difference between the edema conditions before and after the intervention. The findings conclude that cold compress is an effective non-invasive intervention for reducing post-filler edema, with additional benefits of easy application and low cost.